BAGAIMANA SUPERVISI AKADEMIK MENINGKATKAN KINERJA GURU SENIOR DAN JUNIOR - Rani Amrista Wijayanti (Jurnal Evaluasi dan Pembelajaran, 2020)
This research aims to analyze the implementation of academic supervision conducted in one of the private schools in Bandar Lampung. It will examine whether the supervision is able to meet the challenges of the school in developing the teachers’ performance and professionalism both senior and junior teachers. A private school which tends to experiences teachers’ mutation and have new teachers will probably own more challenge to improve the achievement of the school. The teacher is considered to be the main factor to meet this challenge. Therefore, the principal is highly expected to be responsible to monitor the teachers’ performance. In this research, the writer aims to examine whether the supervision conducted has met the goal of the supervision. The result shows that sustainable supervision has effectively conducted by the principal. The supervision was conducted with the following steps: planning, implementation, evaluation, and feedback, and reporting. Based on the result score of the teachers ‘ supervision, it has been concluded that the supervision was conducted not only to fulfill the administrative duty of the principal but it can also to fulfill the goal of supervision to monitor, guide, and improve the teachers’ performances. Besides, in this research, the writer concludes that sustainable supervision has been able to control the performance of both senior and junior teachers. Both the teachers show commitment and a positive response to the implementation of supervision. The result shows that junior teachers have been equally developed as well as senior teachers. Keyword: Supervision, performance, sustainable